2016
DOI: 10.2169/internalmedicine.55.6194
|View full text |Cite
|
Sign up to set email alerts
|

Renal Failure Found during the Follow-up of Sarcoidosis: The Relevance of a Delay in the Diagnosis of Concurrent Hypercalcemia

Abstract: We herein present a case of relapsed sarcoidosis with a deteriorated renal function accompanied by hypercalcemia, nephrolithiasis, and a ureteral stone in a woman with a history of ocular sarcoidosis. The ocular involvement appeared to be well controlled for a long period of time with a topical ophthalmic steroid; however, we believe that the absence of apparent recrudescence could have led to the delay in our diagnosis of relapse of the disease during the follow-up period. The conundrums regarding longitudina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…However, it is difficult to prove the causality between vaccination and AIN because tubulointerstitial nephritis has a wide range of etiologies, including medication (e.g. non-steroidal antiinflammatory drugs, proton pump inhibitors, and antibiotics), autoimmune diseases (such as Sjögren's syndrome, IgG4-related disease, sarcoidosis, and rarely ANCAassociated vasculitis), infection, and tubulointerstitial nephritis and uveitis syndrome (28)(29)(30). In our case, we considered there to be a strong relationship between the SARS-CoV-2 mRNA vaccination and AIN for the following reasons: a persistent fever and AKI within a short duration following vaccination, no other additional medicines prescribed before hospitalization, and few clinical signs suggestive of infection or autoimmune disease at the initial visit.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is difficult to prove the causality between vaccination and AIN because tubulointerstitial nephritis has a wide range of etiologies, including medication (e.g. non-steroidal antiinflammatory drugs, proton pump inhibitors, and antibiotics), autoimmune diseases (such as Sjögren's syndrome, IgG4-related disease, sarcoidosis, and rarely ANCAassociated vasculitis), infection, and tubulointerstitial nephritis and uveitis syndrome (28)(29)(30). In our case, we considered there to be a strong relationship between the SARS-CoV-2 mRNA vaccination and AIN for the following reasons: a persistent fever and AKI within a short duration following vaccination, no other additional medicines prescribed before hospitalization, and few clinical signs suggestive of infection or autoimmune disease at the initial visit.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the production of 1,25-(OH) 2 D 3 by noncaseating granulomas has been implicated in calcium metabolism disorder. An elevated level of 1,25-(OH) 2 D 3 enhances intestinal calcium absorption and promotes osteoclastic activity and bone resorption, resulting in hypercalcemia and hypercalciuria [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Renal failure prevelance range from 0.7% to 4.3% of cases in previous reported clinical series of patients with sarcoidosis but renal failure from granulomatous interstitial nephritis induced nephropathy itself is rare. [6][7][8] A previous study found that 46 of 9,779 (0.5%) renal biopsy specimens had granulomatous interstitial nephritis. The pathology contributing to acute kidney injury from GIN in sarcoidosis is thought to be due to noncaseating granulomatous inflammation, which is composed of a central follicle of macrophages, epithelioid cells, and multinucleated giant cells.…”
Section: Discussionmentioning
confidence: 99%